Taguchi-based optimization of sheeting machine parameters for improved production speed - Putra, William Maha; Martowibowo, Sigit Yoewono; Tabah, Gagan Ganjar (Jurnal Polimesin, 2025)
Sheeting machines play a crucial role in the packaging industry, making parameter optimization essential for enhancing efficiency. This study applies the Taguchi method to optimize key operational factors: roller speed, brake frequency, and pressure. Using ANOM and ANOVA, roller speed was identified as the most influential factor, contributing 82.76% in ANOM and 87.29% in ANOVA, followed by brake frequency (7.08% in ANOM, 7.36% in ANOVA). The F-test (95% confidence interval) confirmed that pressure had an insignificant effect, leading to its exclusion via a pooling-up strategy. Error contributions remained below 15%, ensuring that no critical factors were overlooked. Among interactions, only the roller speed–pressure (A × B) interaction significantly impacted production speed. The optimized parameters increased throughput from 33 to 42 sheets/min (27.3% improvement) and enhanced production robustness (S/N ratio) from 30 to 32.49 (8.3% increase). These findings confirm the effectiveness of the Taguchi method in refining sheeting machine performance.